Retinoblastoma - Clinical Spectrum and Treatment Outcome in Children - Alia Ahmad , Fauzia Shafi Khan , Wasila Shamim , Asif Hanif , Carlos Rodriguez-Galindo, (Journal of Rawalpindi Medical College, 2016)
Background: To analyze outcome of retinoblastoma (RB) in resource limited settings Methods: In this descriptive study , patients of retinoblastoma were treated according to UKCCSG RB 2005 11 protocol with main chemotherapy including Vincristine, Etoposide, Carboplatin and intrathecal Cytarabine called JOE protocol. These protocols were given 3 weeks apart in the chemotherapy bay on outpatient basis. Total 6 courses were given to these patients. The patients presenting with huge tumour with proptosis were offered two courses of chemotherapy (Neoadjuvant) before Enucleation (Removal of orbit and optic nerve) done as upfront Enucleation not possible without mutilating surgery-Exenteration. In our study Group A included patients who refused Enucleation and opted out of recommended treatment plan and Group B patients had Enucleations done and followed treatment plans Results: Total 68 patients with age ranging from< 1 to 7 years (95% <5 yrs) were included. Thirty seven percent presented with bilateral retinoblastoma, fifty six percent with optic nerve involvement and 18% with brain metastasis. 30/68(44%) defaulted treatment, and 33/68 (49%) refused enucleation at diagnosis. Only 3/68(5%) had bilateral enucleation and 50/68(73%) unilateral enucleation with laser therapy in 7/68(10%).Total 52% completed treatment, 26% left against medical advice and 9% expired due to metastatic and progressive disease and sepsis. 9/68 (13%) patients relapsed. Neoadjuvant chemotherapy was given in 59% with 61% of total abandonment and 50% of deaths in this group. The number of bilateral RB was increased to 37% as compared to 18%.Abandonment increased from 13% to 26%. Conclusion: Mortality of 9% can be reduced by early diagnosis and early treatment. Management of RB needs efficient multidisciplinary team and long term sustainable programs to improve survival. The Neoadjuvant group needs extensive follow up and counselling to decrease abandonment.